Role of twinning and texture on fatigue resistance enhancement of Mg-6Gd-3Y-1Nd-0.5Zr alloys. (December 2021) - Luo, An; Deng, Yunlai; Guan, Liqun; Guo, Xiaobin
Highlights: The effect of twinning and texture on the fatigue properties was studied. The law of crack propagation during fatigue was studied. The relationship between grain structure and fatigue resistance was built. Non-basal planes have better resistance to crack propagation. Abstract: The fatigue crack propagation behavior of rolled magnesium alloys was studied and compared with as-cast alloys to unravel a relation between the early crack propagation and the fatigue resistance at the microstructural level. Grain structures results indicated that the geometric compatibility of grains and stress component on basal slip planes determine the propagation path of cracks. Twins are usually unfavorable for crack propagation, and the texture changes the stress component distribution in grains under the condition of unchanged loading. Both twins and textures increase the difficulty of crack propagation and improve the fatigue resistance at higher stress level.